Adsorption studies on ground shells of hazelnut and almond - (:unkn) unknown (ELSEVIER SCIENCE BV, 2007)
Adsorption behaviour of Ni(II), Cd(II) and Pb(II) from aqueous solutions by shells of hazelnut and almond were investigated. The structural properties and surface chemistry of the shells were characterized using sorption of nitrogen and Boehm titration. The equilibrium time was found to be 120 min. The equilibrium adsorption capacity of shells were obtained by using linear Langmuir and Freundlich adsorption isotherms. The equilibrium adsorption level was determined to be a function of the solution contact time, concentration and temperature. The thermodynamic parameters have been determined. The negative values of free change (Delta G) indicated the spontaneous nature of the adsorption of Ni(II), Cd(II) and Pb(II) onto shells of hazelnut and almond and the positive values of enthalpy change (Delta H) suggested the endothermic nature of the adsorption process, The best correlation coefficients were obtained for the pseudo second-order kinetic model. Ion exchange is probably one of the major adsorption mechanisms for binding divalent metal ions to the shells of hazelnut and almond. The selectivity order of the adsorbents is Pb(II) > Cd(II) > Ni(II). (C) 2007 Elsevier B.V. All rights reserved.
Keywords: adsorption; heavy metals; hazelnut; almond; kinetic and thermodynamic parameters; HEAVY-METAL IONS; AQUEOUS-SOLUTIONS; SAWDUST ADSORPTION; MODIFIED BARKS; WASTE-WATER; REMOVAL; SORPTION; COPPER(II); CARBON; RECOVERY